O frazeologii i pragmatemach z perspektywy dydaktyki i translacji - Sułkowska, Monika (Neofilolog, 2023)
The topic of the article is phraseology analyzed from the perspective of didactics and translation. The author presents phraseology as a subject of research and shows its development over time. In the mid-twentieth century, the scope of phraseology mainly encompassed traditional, well-established expressions, such as pictorial phraseologisms, idioms or proverbs. At present, the concept of phraseology has grown significantly, and the research of phraseologists often focuses on structures not typical of traditional phraseology, such as, for example, collocations, multi-word specialist terminology, or reproducible conversational formulas, also known as pragmatemes. In the second part of the text, the author describes the research. Its aim was to find out to what extent philology students are familiar with frequently used pragmatemes. The study was conducted among students of Romance philology at the University of Silesia and covered 50 people. The study used 15 pragmatemes that are often used in modern French communication. The author presents a quantitative and qualitative analysis of the research. It also presents synthetic conclusions that are important in the context of didactics and translation.